Resenha: sugestões didáticas de ensino de sociologia - Feijó, Fernanda (Revista Inter-Legere, 2013)
LIMA, Ângela Maria de Souza; ARAÚJO, Angélica Lyra de; FERREIRA, Jaqueline;MOTTA Silvia Conceição Longuin (orgs.). Sugestões didáticas de ensino de Sociologia. Londrina: UEL, 2012. 470 p.